Host transcriptome response to Mycoplasma bovis and bovine viral diarrhea virus in bovine tissues - Anna K. Goldkamp; Randy G. Atchison; Shollie M. Falkenberg; Rohana P. Dassanayake; John D. Neill; Eduardo Casas (BMC Genomics)
Abstract Background Mycoplasma bovis is a prominent pathogen associated with respiratory disease in livestock. Respiratory disease in cattle often involves co-infection, where a primary viral infection can weaken the host immune system and thus enhance subsequent bacterial infection. The objective of this study was to investigate changes in the host (cattle) transcriptome during bacterial-viral co-infection. RNA sequencing was done in whole blood cells (WBC), liver, mesenteric lymph node (MLN), tracheal-bronchial lymph node (TBLN), spleen, and thymus collected from Control animals (n = 2), animals infected with M. bovis (MB; n = 3), and animals infected with M. bovis and bovine viral diarrhea virus (BVDV) (Dual; n = 3). Results Thymus and spleen had the greatest number of differentially expressed genes (DEGs) out of all tissues analyzed. In spleen, genes involved in maintenance of the extracellular matrix (ECM) including collagen type XV alpha 1 chain (COL15A1), collagen type IV alpha 2 chain (COL4A2), and heparan sulfate proteoglycan 2 (HSPG2) were the most significantly downregulated in Dual compared to Control and MB. In thymus, complement 3 (C3) was a highly significant DEG and upregulated in Dual compared to Control and MB. Interferon alpha inducible protein 6 (IFI6) and interferon-induced transmembrane proteins (IFITM1 and IFITM3), were significantly associated with infection status and upregulated in spleen and thymus of Dual compared to Control and MB. Conclusion Downregulation of ECM components may cause degradation of the ECM and contribute to increased viral spread due to co-infection. Hyperactivation of complement pathway genes may contribute to damage to the thymus and influence severity of co-infection. Co-expression of IFI6, IFITM1 and IFITM3 across lymphoid tissues may be connected to enhanced pathogenesis in co-infection. These findings suggest co-infection exacerbates disease severity through modulation of ECM components in spleen and complement and coagulation cascades in the thymus. These impacted pathways may underlie thymic atrophy and impaired pathogen clearance due to BVDV and M. bovis co-infection.